Innovative Coding Teaching Methodologies: A Comprehensive Approach for Diverse Learners - Beldar, Pankaj; Rakhade, Rahul; Bahiram, Milind; Kadbhane, Snehal (Journal of Engineering Education Transformations, 2025)
This study investigates the pivotal role of coding skills in the education of mechanical engineering students, particularly in areas like data analytics, statistics, and numerical methods. It addresses challenges educators face, such as the abstract nature of programming and diverse student backgrounds, and explores innovative teaching methods such as pair programming and live coding sessions. By equipping students with coding proficiency, the study demonstrates how they can translate complex mathematical algorithms into practical simulations, crucial for analysing mechanical systems like computational fluid dynamics and finite element analysis. The research evaluates the effectiveness of these teaching strategies based on student feedback, emphasizing the need for personalized and innovative approaches to integrate coding effectively into the mechanical engineering curriculum. These insights aim to enhance coding education, preparing students to tackle complex engineering problems, make data-driven decisions, and thrive in today's technological landscape. The study contributes practical implications for educators seeking to bridge the gap between theoretical coding knowledge and its practical application in mechanical engineering, thereby preparing future engineers for the challenges of modern engineering practices.